Perbedaan Edukasi Media Poster Dan Leaflet Terhadap Pengetahuan Keluarga Pasien Tentang Asma Di Wiliyah Kerja Puskesmas Kalirejo Kabupaten Pesawaran - Ajeng Dyah Kumala; M. Arifki Zainaro; Dewi Kusumaningsih (Sekolah Tinggi Ilmu Kesehatan Panca Bhakti, 2026)
Asthma recurrence in the population of all ages in Lampung is relatively high. Based on the proportion of asthma recurrence in the population of all ages throughout the province, Lampung is in 4th position with a proportion of recurrence of 64.7%. This shows that asthma control in Lampung is relatively low. Based on data from the pre-survey interview results of home visits, on December 9, 2024 at the Kalirejo Health Centre there were 15 respondents, 10 respondents already knew family knowledge about asthma and 5 respondents did not know family knowledge about asthma, so there was a lack of knowledge and an increase in the occurrence of asthma from the previous year. To determine the effect of poster and leaflet media education on the knowledge of patient families about asthma in the Kalirejo Health Centre Work Area, Pesawaran Regency. Quantitative research type. The quasi-experimental design used was one group pretest-posttest. The sample was 30 respondents. The sampling technique was purposive sampling. Data analysis used univariate and bivariate using dependent t-test. The average knowledge of patient families about asthma before being given poster and leaflet media education with a mean of 11.60 after being given poster and leaflet media education with a mean of 15.80 p-value 0.000 <0.05. There is an effect of poster and leaflet media education on the knowledge of patient families about asthma in the Kalirejo Health Centre Work Area, Pesawaran Regency.